Biogas to Energy in Rural Romania. Scenarios of Sustainable Development - CRISTIAN-MARIUS MOISOIU (Global Economic Observer)
This paper presents four exploratory scenarios of sustainable development using the biogas to energy in animal farms in Romania. This research was part of the doctoral thesis of the author, entitled “The Economic Impacts of Climate Change”. The biomass sector is one of the most promising, but less developed fields of the Romanian energy sector. Based on a sectoral analysis of the biomass in Romania, with regards to the transition process towards the low-carbon economy, few scenarios were drafted, in order to provide the decision makers with eventual prospects and drivers in the field, in order to overcome with relevant policies. The study responds to the European Union’s climate action, resource efficiency and raw materials priority and climate change mitigation effort, together with fostering renewable energy technologies.